News Objectivity and Journalism Ethics in Online Media: Case on BUMN Employees Recruitment (Obyektivitas Berita dan Etika Jurnalistik di Media Online: Kasus Rekrutmen Karyawan BUMN) - Christiany Juditha (BBPSDMP KOMINFO MAKASSAR, 2016)
The rapid development of the Internet led to the online media business is also growing rapidly in Indonesia. However, this raises another issue between the lack of quality and credibility of information to the public. In addition, online media journalists also less notice journalistic ethics. The information has not been verified finals already reach a wide audience, so sometimes cause mis-perceptions and mis-interpretation. One of them is the issue of banning headscarves news on BUMN employee recruitment. Purpose of this research is to gain an overview of journalism ethics and objectivity news in online media about BUMN employee recruitment. The method used is content analysis with a qualitative approach. The results of this study concluded that some online news sites like Okezone.com, Sindonews.com, Goriau.com, Tribunnews.com, and Republika Online Harianterbit initially contain information that comes from only one source, namely Twitter account @estiningsihdwi about about banning headscarves in recruitment of employees in BUMN without ensure the correctness or authenticity of the documents posted the account. Objectivity like no check and re-check, in favor of one party, does not cover both sides and unbalanced occur in the news. Although some of these media sites then finally provide clarification of the Ministry of BUMN’s were denied the issue.Perkembangan internet di Indonesia yang sangat pesat menyebabkan bisnis media online juga bertumbuh cepat. Namun hal ini menimbulkan masalah antara lain minimnya kualitas dan kredibilitas informasi yang sampai ke masyarakat. Selain itu etika jurnalistik juga kurang diperhatikan oleh para jurnalis media online. Informasi yang belum final terverifikasi sudah sampai kepada masyarakat luas sehingga menimbulkan mis-persepsi dan mis-interpretasi. Salah satu diantaranya adalah isu berita pelarangan berjilbab pada perekrutan karyawan BUMN. Tujuan penelitian ini adalah untuk mendapatkan gambaran tentang objektifitas berita dan etika jurnalistik di media online tentang perekrutan karyawan BUMN. Metode penelitian yang digunakan adalah analisis isi dengan pendekatan kualitatif. Hasil penelitian ini menyimpulkan bahwa beberapa situs berita online seperti Okezone.com, Sindonews.com, Goriau.com, Tribunnews.com, Harianterbit dan Republika Online awalnya memuat informasi yang berasal dari hanya satu sumber yaitu akun Twitter @estiningsihdwi tentang pelarangan berjilbab pada rekrutmen karyawan BUMN tanpa memastikan kebenaran atau keaslian dokumen yang diposting akun tersebut. Objektivitas seperti tidak ada cek dan ricek, berpihak pada satu pihak, tidak cover both sides dan tidak berimbang juga terjadi dalam pemberitaan. Meski beberapa situs media ini kemudian akhirnya memberikan klarifikasi dari Kementerian BUMN yang membantah isu tersebut.